A Klebsiella pneumoniae NDM-1+ bacteriophage: Adaptive polyvalence and disruption of heterogenous biofilms - Gilcrease, Eddie B.; Casjens, Sherwood R.; Bhattacharjee, Ananda; Goel, Ramesh (Frontiers in Microbiology, 2023)
Bacteriophage KL-2146 is a lytic virus isolated to infect Klebsiella pneumoniae BAA2146, a pathogen carrying the broad range antibiotic resistance gene New Delhi metallo-betalactamase-1 (NDM-1). Upon complete characterization, the virus is shown to belong to the Drexlerviridae family and is a member of the Webervirus genus located within the (formerly) T1-like cluster of phages. Its double-stranded (dsDNA) genome is 47,844 bp long and is predicted to have 74 protein-coding sequences (CDS). After challenging a variety of K. pneumoniae strains with phage KL-2146, grown on the NDM-1 positive strain BAA-2146, polyvalence was shown for a single antibiotic-sensitive strain, K. pneumoniae 13883, with a very low initial infection efficiency in liquid culture. However, after one or more cycles of infection in K. pneumoniae 13883, nearly 100% infection efficiency was achieved, while infection efficiency toward its original host, K. pneumoniae BAA-2146, was decreased. This change in host specificity is reversible upon re-infection of the NDM-1 positive strain (BAA-2146) using phages grown on the NDM-1 negative strain (13883). In biofilm infectivity experiments, the polyvalent nature of KL-2146 was demonstrated with the killing of both the multidrug-resistant K. pneumoniae BAA-2146 and drug-sensitive 13883 in a multi-strain biofilm. The ability to infect an alternate, antibiotic-sensitive strain makes KL-2146 a useful model for studying phages infecting the NDM-1+ strain, K. pneumoniae BAA-2146.